Conductive Polymer–Exoelectrogen Hybrid Bioelectrode with Improved Biofilm Formation and Extracellular Electron Transport. (27th June 2019) - Zhang, Pengbo; Zhou, Xin; Qi, Ruilian; Gai, Panpan; Liu, Libing; Lv, Fengting; Wang, Shu
Abstract: Low organism loading capacity and inefficient extracellular electron transport (EET) are still the bottlenecks hindering the development of bioelectrochemical systems (BESs). It is shown that cationic polythiophene derivative (PMNT) has the ability to simultaneously enhance bacteria biofilm formation, improve the bacteria viability, decrease the resistance value, and accelerate the EET process between exoelectrogen and the electrode. Shewanella oneidensis can form a robust and thick biofilm on the electrode surface in the presence of PMNT. Mediated by electron‐transporting PMNT, even bacteria far away from the electrode can transfer electrons to it. This bioelectrode is utilized as the anode to construct a microbial fuel cell, which exhibits a greatly increased maximum current density and power density and a prolonged lifetime by taking advantage of the unique properties of PMNT. Thus, cationic conductive polymers exhibit great potential as effective biofilm enhancers and electron transporters in BESs. Abstract : Cationic polythiophene derivative (PMNT) has the ability to simultaneously induce bacteria biofilm formation, improve the bacteria viability, and accelerate the extracellular electron transport (EET) process. Utilizing a conductive polymer–exoelectrogen hybrid bioelectrode as anode in microbial fuel cells (MFCs) increases the maximum current density and power density and prolongs the MFCs' lifetime.